The dimensions and practices of talent management and its role in enhancing the efficiency and effectiveness of human resources management: A theoretical analytical study - Al- Rakhis, Fatima Mohammad; Al- Rakhis, Maha Mohammad (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to examine the dimensions and practices of talent management and its role in enhancing the efficiency and effectiveness of human resource management, a theoretical analytical study, and by attempting to answer the main question of the study and the sub- questions of the research problem, and by relying on the descriptive, analytical and theoretical approach of previous literature in this field through four hypotheses that were examined. The results of the study revealed that there is a relationship between talent management practices and the efficiency and effectiveness of human resources management, in addition to a relationship between talent management practices in terms of discovery, retention and development of talented people and the efficiency and effectiveness of human resources management and the validation of the four hypotheses. Talents according to a long- term strategic plan that focuses on performance indicators that increase added value and support institutional sustainability, while directing talent management practices to enhance the efficiency and effectiveness of human resource management performance.
Keywords: talent management; talent management practices; talent discovery; talent retention; talent development; efficiency and effectiveness of human resource management